The use of 3D biomodels in the learning of human anatomy: a technical and methodological experience (Research, Society and Development, 2022)
Introduction: The use of active methodologies in health education has been widespread in recent years, in order to overcome the difficulties faced by students in the first years of academic life. Objective: To report an experience of creating and using 3D biomodels in the learning of Human Anatomy, for students of the 1st period of the Pharmacy and Nursing courses at the Federal University of Piauí. Experience report: 65 students participated, all duly enrolled in the discipline of human anatomy, from the 1st period of the respective courses of the aforementioned university. Then, they were divided into groups responsible for an anatomical piece, making a total of eight pieces. The teachers tried to choose bones that were more difficult to obtain in their real form, such as: the sphenoid, the ethmoid and the small bones of the hand, respecting the bordering impression dimensions of the equipment. The pieces were presented in the classroom and through creative videos produced directly by the students on social networks. All models were made using a 3D SLA/LCD printer using light-curing resin. Conclusion: This experience proved to be effective for bringing a playful perspective to learning with detailed structures, close to the real ones. It was a dynamic approach that enabled greater understanding and retention of the content. In addition, propagation in virtual environments contributed to the dissemination of knowledge quickly and practically, reaching a large audience and increasing the probability of encouraging new projects and activities in the same area.